Sistem Pengecekan Toko Online Asli atau Dropship pada Shopee Menggunakan Algoritma Breadth First Search - Nurdin; Muhammad Hutomi; Mukti Qamal; Bustami Bustami (Ikatan Ahli Informatika Indonesia (IAII), 2020)
The abundance of online shops on web ecommerce Shopee's makes it difficult for consumers to detect the genuineness of an online store. Online store detection app is an application to detect genuine online shop, good rating online shop, and fake online shop, which is useful as a recommendation to consumers in buying a product against an online shop. Detection by implementing the Breadth First Search (BFS) algorithm with Web Scraping techniques against Web e-commerce Shopee with the keyword